The Negro Grandsons of Vercingetorix - Mabanckou, Alain, 1966- (Global African voices., 2019)
Set in the imaginary African Republic of Vietongo, The Negro Grandsons of Vercingetorix, begins when conflict breaks out between rival leaders and the regional ethnic groups they represent. Award-winning author Alain Mabanckou is at his satiric best in this novel that catalogues the pain and suffering caused by the ravages of civil war.